Анализ приемной системы лидара - Калашник, В. М. (ХНУРЕ, 2020)
Widespread use of lidar systems for atmospheric location impurities require optimization of its main components. Special meaning It has optimization of the lidar receiving antenna, the weight and manufacturing cost of which is related to the area of the telescope's main mirror. The parameters of the receiving antenna largely determine the characteristics of the lidar as a whole. An increase in the diameter of the receiving antenna leads to an increase in the number of both signal and background photoelectrons.
Keywords: lidar system; lidar receiving antenna